Application of binary image in digital audio watermarking - Aishwarya Visvanathan (2009)
Digital watermarking has been proposed as a means to identify the owner or distributor of digital data. The process of embedding information into another object/signal can be termed as watermarking which is carried out by making small modifications to the data samples without the loss of quality. A watermark is designed to permanently reside in the host data. Whenever the copyright of a digital object is in question, this information is extracted to identify the rightful owner. It is also possible to encode the identity of the original buyer along with the identity of the copyright holder, which allows tracing of any unauthorized copies. Digital audio watermarking, involves the concealment of data within a discrete audio file. Applications for this technology arc numerous. Intellectual property protection is currently the main driving force behind research in this area. Other non-rights related uses for watermarking technology include embedding auxiliary information which is related to a particular song, like lyrics, album information, or a small web page, etc. Watermarking could be used in voice conferencing systems to indicate to others which party is currently speaking. A video application of this technology would consist of embedding subtitles or closed captioning information as a watermark. In this project an in-depth analysis of the various audio watermarking schemes has been carried where a visually recognizable binary image is used as the watermark. A binary image has been chosen as the watermark, rather than a random sequence, since an image is easily recognizable and it helps the owner to embed his/her company logo or name as the watermark information, which is clearly visible, and helps in better security. The watermark embedding process and its retrieval have been discussed in this report.